Pengaruh Perceived Ease Of Use Dan Harga Terhadap Kepuasan Konsumen Pengguna Aplikasi Maxim : The Effect of Perceived Ease of Use and Price on Consumer Satisfaction of Maxim Application Users - Fani Oktafiona; Safitri, Syofiatul (Jurnal Ilmiah Produktif, 2025)
This study aims to examine the influence of Perceived Ease of Use (PEOU) and Price on Customer Satisfaction among Maxim application users, particularly those in the Faculty of Social and Political Sciences at the University of Riau. The research employed a quantitative method, involving 96 respondents selected through purposive sampling based on specific criteria. Data analysis was conducted using SPSS version 30. The analysis results indicate that PEOU has a positive and significant partial effect on customer satisfaction, as evidenced by a t-value of 5.748 and a significance level below 0.001. The Price variable also showed a significant partial effect, with a t-value of 2.820 and a significance value of 0.006. Collectively, both PEOU and Price have a positive and significant impact on customer satisfaction, as indicated by an F-value of 79.669, which exceeds the F-table value of 3.09. These findings suggest that both Perceived Ease of Use and Price play an important role in enhancing the satisfaction of Maxim users.